Experiment-based cause analysis of secondary explosion of ammonium nitrate in fire conditions. (July 2022) - Wang, Xu; Pei, Chenxi; Wu, Xingliang; Xu, Feiyang; Yang, Nian; Liu, Dabin; Xu, Sen
Abstract: Ensuring adequate safety during the production, transportation and storage of ammonium nitrate (AN) has always been a matter of concern. In particular, the combustion and explosion of other chemicals in fire conditions could lead to secondary explosions of AN. An understanding of the effect of fire conditions on the blast characteristics of AN and an estimate of the blast characteristic parameters of AN, such as the critical detonation pressure and fragment impact response, are necessary for minimising risks associated with the large-scale storage of AN and AN-based fertilisers at ports and for avoiding secondary explosions. In this study, the blast characteristic parameters of AN were determined by conducting the UN gap test and fragment impact test. An increase in the AN temperature from −20 °C to 140 °C was found to be accompanied by a gradual decrease in the critical detonation pressure from 5.444 GPa to 1.741 GPa. Furthermore, bombardment by high-speed fragments caused the ignition of AN below 60 °C, and when the temperature reached 100 and 140 °C, deflagration and explosion occurred, respectively. When combined with the results of an assessment of an explosion event at Tianjin Port, these results indicate that the bombardment of AN by metal fragments produced by an explosion is likely to trigger secondary explosions. Highlights: The main reason for secondary explosions of AN in fire conditions was analyzed. Temperature dependence of shock wave sensitivity of AN was investigated. Temperature dependence of fragment impact response grades was investigated.